Leptin promotes a proinflammatory lipid profile and induces inflammatory pathways in human SZ95 sebocytes - Törőcsik Dániel; Kovács Dóra; Camera Emanuela; Lovászi Marianna; Cseri Karolina; Nagy Georgina G.; Molinaro Raphael; Rühl Ralph; Tax Gábor; Szabó Kornélia Ágnes; Picardo Mauro M.; Kemény Lajos; et al. (2014)
Our findings suggest that leptin signalling may be involved in the proinflammatory regulation of sebaceous lipid metabolism and the induction of inflammatory enzymes and cytokines.